Economic reconstruction of industrial macroregions of Ukraine on the basis of public-private partnership in the conditions of war and post-war recovery - Shylepnytskyi, P.I.; Petrova, I.P. (Економічний вісник Донбасу, 2025)
The article substantiates the conceptual model of economic reconstruction of industrial macroregions of Ukraine in the conditions of war and post-war recovery on the basis of public-private partnership (PPP). It is shown that the large-scale destruction of production facilities, logistics hubs and critical infrastructure necessitates the transition from fragmented restoration measures to systemic macroregional reconstruction, oriented on the principle of build back better, structural transformation of industry and increasing the resilience of the economy. It is proposed to consider the reconstruction of industrial macroregions as an integrated combination of infrastructure, industrial and innovation contours, which ensures the coordination of the restoration of basic networks, modernization of production potential and the formation of long-term sources of economic growth. Relevant PPP models for reconstruction and modernization projects are systematized depending on their functional purpose and level of risks; the feasibility of a portfolio approach to the implementation of PPP at the macroregional level is substantiated. A risk matrix of PPP projects has been formed, taking into account military, fiscal, market, institutional and climatic factors, and the principles of their distribution between public and private partners have been determined in accordance with the risk management capacity. A roadmap for the implementation of the PPP project portfolio in the macro-regional dimension has been developed, adapted to the specifics of the Dnieper region as a key industrial region of Ukraine. У статті обґрунтовано концептуальну модель економічної реконструкції промислових макрорегіонів України в умовах війни та повоєнного відновлення на засадах публічно-приватного партнерства (ППП). Показано, що масштабні руйнування виробничих потужностей, логістичних вузлів і критичної інфраструктури зумовлюють потребу переходу від фрагментарних відновлювальних заходів до системної макрорегіональної реконструкції, зорієнтованої на принцип build back better, структурну трансформацію промисловості та підвищення резильєнтності економіки. Запропоновано розглядати реконструкцію промислових макрорегіонів як інтегроване поєднання інфраструктурного, індустріального та інноваційного контурів, що забезпечує узгодження відновлення базових мереж, модернізації виробничого потенціалу та формування довгострокових джерел економічного зростання. Систематизовано релевантні моделі ППП для проєктів відбудови й модернізації залежно від їх функціонального призначення та рівня ризиків; обґрунтовано доцільність портфельного підходу до впровадження ППП на макрорегіональному рівні. Сформовано матрицю ризиків проєктів ППП з урахуванням воєнних, фіскальних, ринкових, інституційних і кліматичних чинників та визначено принципи їх розподілу між публічним і приватним партнерами відповідно до спроможності управління ризиками. Розроблено дорожню карту впровадження портфеля проєктів ППП у макрорегіональному вимірі, адаптовану до специфіки Придніпров’я як ключового промислового регіону України.